2021
DOI: 10.3390/v13061147
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tsg101 Binding Partners Regulate Viral L Domain Trafficking

Abstract: Two decades ago, Tsg101, a component of the Endosomal Sorting Complexes Required for Transport (ESCRT) complex 1, was identified as a cellular factor recruited by the human immunodeficiency virus type 1 (HIV-1) to facilitate budding of viral particles assembled at the cell periphery. A highly conserved Pro-(Thr/Ser)-Ala-Pro [P(T/S)AP] motif in the HIV-1 structural polyprotein, Gag, engages a P(T/S)AP-binding pocket in the Tsg101 N-terminal domain. Since the same domain in Tsg101 that houses the pocket was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 93 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…The UEV domain of Tsg101 resembles canonical E2 Ub-conjugating enzymes but is unable to catalyze Ub transfer because it lacks the active site cysteine that forms the transient thioester bond with the C terminus of Ub ( 26 , 27 ). Moreover, it binds Ub but at novel sites that are not fully equivalent to that in canonical E2s ( 24 , 25 , 28 ). Still, given the similarities, we initially probed for evidence of a direct interaction between the Nedd4-1 HECT domain and the Tsg101 UEV domain at three sites ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UEV domain of Tsg101 resembles canonical E2 Ub-conjugating enzymes but is unable to catalyze Ub transfer because it lacks the active site cysteine that forms the transient thioester bond with the C terminus of Ub ( 26 , 27 ). Moreover, it binds Ub but at novel sites that are not fully equivalent to that in canonical E2s ( 24 , 25 , 28 ). Still, given the similarities, we initially probed for evidence of a direct interaction between the Nedd4-1 HECT domain and the Tsg101 UEV domain at three sites ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The UEV domain of Tsg101 is highly similar to E2 ligases, albeit without the active site cysteine ( 28 ). The PRE data obtained at all sites show a weak preference for the β-hairpin region from residues 40 to 50 of the UEV domain, and crucially, for a region between T99 and H115 that lies proximal to the vestigial E2 active site.…”
Section: Discussionmentioning
confidence: 99%
“…TSG101 is a highly conserved protein in mice and humans, and is a component of the ESCRT machinery [ 27 ]. Although it was first reported as a virus-binding protein [ 28 ], it has recently been shown that TSG101 plays important roles in recognizing and sorting ESCRT cargo [ 29 ]. The biogenesis and secretion of exosomes is mainly regulated by the ESCRT machinery.…”
Section: Discussionmentioning
confidence: 99%
“…[8,24] Screening of commercially available prazoles found that larger compounds (rabeprazole and ilaprazole) are generally more effective at inhibiting viral egress, where this may stem from more rapid conversion to the active form, or from the larger prazole adduct on the Tsg101 UEV domain providing a more effective blockade of Ub-binding. [9,25] To test this further, here we screened 20 prazole-derivatives, both in vitro for differences in their binding to Tsg101, and in the cell, where we identified 10 compounds as having < 5 μm IC50 against HIV-1 and identified SARS-COV-2 as a further target of prazole-based inhibition. Structurally, we find that increased bulk on the 4-pyridyl substituent of the prazole expands its impact on the UEV domain toward the 𝛽-hairpin in the Ub-binding site, which is coupled to increased inhibition of virus-like particle (VLP) production in HIV-1.…”
Section: Introductionmentioning
confidence: 99%